2013
DOI: 10.1371/journal.pone.0064334
|View full text |Cite
|
Sign up to set email alerts
|

GFP Transgenic Medaka (Oryzias latipes) under the Inducible cyp1a Promoter Provide a Sensitive and Convenient Biological Indicator for the Presence of TCDD and Other Persistent Organic Chemicals

Abstract: Persistent organic pollutants (POPs) are resistant to environmental degradation and can cause multitude of health problems. Cytochrome P450 1A (Cyp1a) is often up-regulated by POPs through the activation of aryl hydrocarbon receptor (AhR) pathway and is thus usually used as a biomarker for xenobiotics exposure. To develop a convenient in vivo tool to monitor xenobiotic contamination in the water, we have established GFP transgenic medaka using the inducible cyp1a promoter, Tg(cyp1a:gfp). Here we tested Tg(cyp1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Although the LOECs for other metals are significantly higher than the EPA's MLCs, the GFP transgenic medaka still offer a convenient, economical, and potentially online sentinel system for aquatic environmental pollution. However, a major weakness of the GFP-based assay is the difficulty for quantification of GFP fluorescence and the problem can be partially overcome by quantification of the number of GFP positive individuals and/or by objective classification of strong/weak GFP expression as we previously described (Zeng et al 2005;Ng and Gong 2013).…”
Section: Differential Gfp Expression Patterns Induced By Different Hementioning
confidence: 99%
See 1 more Smart Citation
“…Although the LOECs for other metals are significantly higher than the EPA's MLCs, the GFP transgenic medaka still offer a convenient, economical, and potentially online sentinel system for aquatic environmental pollution. However, a major weakness of the GFP-based assay is the difficulty for quantification of GFP fluorescence and the problem can be partially overcome by quantification of the number of GFP positive individuals and/or by objective classification of strong/weak GFP expression as we previously described (Zeng et al 2005;Ng and Gong 2013).…”
Section: Differential Gfp Expression Patterns Induced By Different Hementioning
confidence: 99%
“…In recent years, several transgenic fish with fluorescence protein reporters have been established for pollution detection because of its easy, on site, and real-time detection of fluorescence signal in living cells and organisms (Blechinger et al 2002;Chen et al 2010;Kurauchi et al 2008;Kusik et al 2008;Salam et al 2008;Wu et al 2008;Zeng et al 2005;Ng and Gong 2013). Transgenic fish, like an in vivo system, reflects not only the bioaccumulation of toxicants but also the toxicity to targeted organs.…”
Section: Introductionmentioning
confidence: 99%
“…The promoter of the cyp1a1 gene has been used to drive a GFP reporter gene for measuring exposure to organic chemicals in both transgenic zebrafi sh and medaka (Hung et al 2012, Ng and Gong 2013. Cyp1a1 is a cytochrome P450 enzyme involved in the oxidative metabolism of various organic substances including polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs).…”
Section: Cyp1a1 Promotermentioning
confidence: 99%
“…Transgenic fi sh have been developed as model systems for understanding genetics mechanisms and developmental processes and for pharmaceutical discovery (target validation), safety assessment and bio-synthesis (Dunham 2009, Moro et al 2012, Nguyen et al 2012. They have also been created to study-specifi c processes in fi sh including cold tolerance and for enhancing both disease resistance and growth rate in aquaculture species (Devlin et al 2004, Du et al 1992, Dunham 2009, Wang et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, functional assays demonstrate AhR transactivation as early as 6 hpf in tg(cyp1a:gfp) medaka (Ng and Gong, 2013), where cyp1a induction serves as a sensitive marker of AhR activation. Numerous studies have reported the teratogenic effects of TCDD in multiple organ systems in medaka and zebrafish following developmental exposure (King-Heiden et al, 2012).…”
mentioning
confidence: 99%